Care and Working Together: A Case Study of a School where Spanish-speaking English Language Learners Succeed. - Diez, Virginia. (2017)
Abstract: This case study examines the proposition that caring teachers and culturally-relevant pedagogy can have an impact on the positive academic outcomes of Spanish-speaking English Language Learners (SPELLs). For this purpose, an urban school where SPELLs achieved higher educational outcomes than similar children in similar district schools was studied using an interpretive, phenomenological framework. Findings confirmed extant literature that caring is entwined with culturally-relevant practice. Findings also showed that caring and culturally-savvy administrators held strength-based conceptions of students' differences, and made programmatic and policy choices designed to address all students' learning needs. Administrators also used "working together" as an educational strategy aimed at both students and teachers. Working together had many of the characteristics of joint activity (Cole, 1996, Gallimore & Goldenberg, 2001, Rogoff, 2003). Students, especially those at risk, worked together with expert adults in small support groups, and had access to adult mentors. Teachers, in turn, were involved in joint activities with administrators and coaches who guided their professional development. The study suggests that joint activity between experts and novices was a mechanism linking caring and cultural relevance to positive student outcomes, as well as to changes in school culture. Theoretical and practical implications for school reform are discussed.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Child Development.; Advisors: Calvin Gidney, and Jayanthi Mistry.; Committee: Jayanthi Mistry, Miren Uriarte, and Eleonora Villegas-Reimers.; Keywords: Bilingual education, Teacher education, and Hispanic American studies.